Flood warning system: a cost- benefit analysis of the northern Bangladesh - Hasan, Mohammad Kamrul (BRAC Univeristy, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2018.